History of the Study of Folklore Ethnografisms (Eurasian Research Bulletin, 2023)
Folk oral poetic creativity-verbal word art is referred to as "folklore" or "folkloristics". Folkloristics has been considered part of ethnography, sometimes anthropology, sometimes musicology, and even sociology at different times and in different countries. The article discusses the study of ethnografisms of folklore in the world and Uzbek linguistics.